WE CAN’T BE FRIENDS: THE CHANGE OF PUBLIC PERCEPTION TOWARD ARIANA GRANDE - Florencia, Florencia (Serat: Journal of Literary & Cultural Studies, 2025)
The public's perceptions of celebrities could easily turn from loving to hating. Changes in personal life, public image, and the rapid spread of information contribute to the formation of public opinion. This study aims to analyze the public's perception of a public figure, focusing on the song ‘We Can’t Be Friends’ by Ariana Grande using qualitative methods. The objective of this research is to explain the lyrics of the song, which present the constant scrutiny the singer experienced and the criticism she received after a few controversies she had. Furthermore, this paper discusses the implications of these perceptions and their impact on relationships with fan communities. The study also includes supporting factors influencing opinions, such as the celebrity persona, cultural background, controversy, and previous work. By the end, we understand how these factors could shape public opinion, examine how community sentiment shifted, and determine the interpretation of the song.